Never the Twain Shall Meet? : Latins and Greeks learning from each other in Byzantium. - Searby, Denis (Byzantinisches Archiv. Series philosophica., 2017)
Byzantinisches Archiv - Series Philosophica is dedicated to the new and rapidly growing field of research into Byzantine philosophical texts. It considers itself a forum for cutting-edge research on Byzantine philosophy based on solid philological and historical foundations. Its aim is to publish conference volumes, monographs and critical editions. High quality standards are ensured through anonymous reviewing.